Abnormalities on neurological examination among sheep farmers exposed to organophosphorous pesticides. - Beach, J R (1996)
OBJECTIVES: Organophosphates are effective pesticides which are frequently used in several agricultural settings. Although their acute effects are well characterised, it remains unclear whether long term exposure can damage the human nervous system. This study sought to investigate their long term effects by comparing abnormalities on neurological examination between groups of workers exposed to organophosphates and an unexposed group. METHODS: 146 exposed sheep farmers and 143 unexposed quarry workers were recruited into a cross sectional study of symptoms and neuropsychological effects of long term exposure to organophosphates in sheep dip. From a symptom questionnaire given immediately after dipping the 10 most symptomatic and 10 least symptomatic farmers were selected. Several months later each of these, along with 10 of the unexposed quarry workers, underwent a standardised neurological examination similar to that which might be used in clinical practice, at at time as remote as possible from recent exposure to organophosphates so as to exclude any acute effects. RESULTS: All 30 selected subjects agreed to participate. The components of the examination which showed a significant difference were two point discrimination on the dorsum of the hand (symptomatic farmers 22 mm; asymptomatic farmers 13 mm; quarry workers 8 mm) and the dorsum of the foot (symptomatic farmers 34 mm; asymptomatic farmers 10 mm; quarry workers 11 mm), and mean calf circumference (symptomatic farmers 35.0 cm; asymptomatic farmers 36.3 cm; quarry workers 38.6 cm). Overall the prevalence of neurological abnormalities was low. CONCLUSIONS: The differences in neurological examination detected between groups were subtle and their clinical significance was unclear. However, they do suggest evidence of an adverse neurological effect from exposure to organophosphates. Further, larger scale studies will be required before it is possible to confirm or refute the differences detected.